2003
DOI: 10.1097/00005176-200307000-00014
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Feeding Problems in 700 Infants and Young Children Presenting to a Tertiary Care Institution

Abstract: A multidisciplinary team approach is essential for assessment and management because combined medical and oral problems are the most frequent cause of pediatric feeding problems. A significant relationship was found between the type of feeding problem and age. Infants born preterm and/or with a birthweight below the tenth percentile for gestational age are at greater risk for developing feeding disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
265
1
36

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(322 citation statements)
references
References 15 publications
20
265
1
36
Order By: Relevance
“…15 A study of 700 children under the age of 10 who had feeding disorders diagnosed found that medical disorder and behavioral problems related to feeding occurred both alone and in combination: 86% had an underlying medical disorder, 61% had some oropharyngeal dysfunction, and 18% had a behavioral problem. 16 Budd and colleagues also reported that 64% of their sample of children presenting for out-patient treatment of feeding problems had a combination of behavior disturbance and subtle oral-motor problems. 17 To some extent, such figures are determined by the type of clinical setting where the study is carried out, making it difficult to clarify the interplay between physical and psychological factors and even more difficult to disentangle cause and effect.…”
Section: Feeding Disorder Of Infancy or Early Childhoodmentioning
confidence: 99%
“…15 A study of 700 children under the age of 10 who had feeding disorders diagnosed found that medical disorder and behavioral problems related to feeding occurred both alone and in combination: 86% had an underlying medical disorder, 61% had some oropharyngeal dysfunction, and 18% had a behavioral problem. 16 Budd and colleagues also reported that 64% of their sample of children presenting for out-patient treatment of feeding problems had a combination of behavior disturbance and subtle oral-motor problems. 17 To some extent, such figures are determined by the type of clinical setting where the study is carried out, making it difficult to clarify the interplay between physical and psychological factors and even more difficult to disentangle cause and effect.…”
Section: Feeding Disorder Of Infancy or Early Childhoodmentioning
confidence: 99%
“…It is known that an infant's medical condition 11 and neurological maturity 6,12 influence nutritive sucking. Behavior state has also been shown to have a relationship to sucking activity.…”
Section: Introductionmentioning
confidence: 99%
“…A definição da complexidade da atenção nutricional pode contribuir para o estabelecimento de prioridades, uma vez que as demandas de cuidados hospitalares necessitam ser gerenciadas, além disso, faz-se necessária a caracterização dos problemas e dificuldades que envolvem o paciente para que o cuidado seja direcionado 12 .…”
Section: N T R O D U ç ã Ounclassified